PERAN ORANG TUA DALAM PENGEMBANGAN MODERASI BERAGAMA PADA ANAK USIA DINI - Subandi, Sri Asmanah; Khojir, Khojir; Suratman, Suratman (TARBAWI:Journal on Islamic Education, 2023)
The purpose of this study is to describe the role played by parents in an effort to develop religious moderation in early childhood within the family sphere. The method used in this research is qualitative with a literature study approach. The literature used is books and articles about religious moderation in early childhood. Data collection techniques are carried out by exploring matters or variables related to religious moderation and the involvement of parents and early childhood in it. The data analysis technique used is a content analysis model on data obtained from readings on religious moderation in early childhood. The study results show that the values of religious moderation instilled in early childhood are national commitment, tolerance, anti-radicalism, and accommodative. The forms of the role of parents in the development of religious moderation in early childhood are media filters used by children, telling the good stories of the Prophets and Apostles, teaching respect, respect, and tolerance with others, and setting an example through example and habituation of good behavior.